Use of combination method (uterine sandwich technique) to control postpartum hemorrhage - Dhillon, Atmajit Singh; Dhillon, Karminder (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Uterine atony is the most common cause (75%-90%) of primary postpartum hemorrhage (PPH) and Christopher B Lynch was the first to highlight the use of Uterine Compression Sutures (UCS) for the management of atonic PPH. In combination therapy, the (UCS) is combined with intrauterine balloon tamponade, known as (uterine sandwich), for combined external as well as internal compression for more effective hemostatic control of uterine bleeding. Methods: The uterine sandwich technique was used in a total of twelve patients managed in a tertiary care service hospital during caesarean deliveries. In four cases of uterine atony, the sandwich technique was used, for patients unresponsive to the conservative management. In eight patients the sandwich technique was used as a prophylactic measure, where according to the clinical profile of the patient there was high risk of PPH and where either blood was not available or availability was limited. Results: In the four cases of uterine atony, the uterine sandwich technique was used therapeutically. All the patients were multigravidae. The period of gestation ranged from 34 weeks to 37 weeks. Average operating time was 50- 60 mts, average estimated blood loss was 1600 ml, average distension of Foleys catheter was 90 ml and average duration of the intrauterine Foleys catheter balloon being in situ was 12 hrs. In eight patients, the sandwich technique was used as a prophylactic measure, for varied indications. In all the cases there was successful outcome. Post-operative outcome was uneventful in all the cases. Conclusions: The uterine sandwich technique can be used either prophylactically or therapeutically for control of PPH. It is simple, safe, easy, effective and is easier to perform than internal iliac artery ligation and should be considered prior to proceeding for hysterectomy in a hemodynamically stable patient, in whom uterine conservation or fertility preservation is essential.